Evolution of the martensitic transformation in shape memory alloys under high strain rates - Pattofatto S.; Saletti D.; Zhao H. (EPJ Web of Conferences, 2010)
The speciﬁc properties of the shape memory alloys are mainly due to the martensitic transformation occuring in the material when mechanical or thermal loadings are applied. Here, the eﬀect of strain rate on the transformation on an NiTi SMA is studied in tension. Diﬀerent tests were performed at diﬀerent strain rates in the range of 0,0001 /s to 15 /s. Two distinct methods were used to measure the extension rate of the martensitic phase region in the specimen: digital image correlation technique and infrared thermography (IR during quasi-static tensile tests only). For the dynamic tensile tests, a Split Hopkinson Tensile Bar set-up was used with a fast camera recording at 45’000 fps. A superimposition of DIC and IR measurements in time and space can be done during quasi-static tests and results show that the temperature peak, as expected, follows the transformation front. As a consequence of the former validation of the DIC procedure, the velocity of the transformation front at high strain rate is deduced from space-time ﬁgures. As a conclusion, in the range of strain rates investigated in this paper, no strain rate sensitivity is observed for dynamics of extension of the transformation region.